Comparison CSAI-2 and Frontal Muscle EMG According to Performance Result and Gender in Fencing Epee University Athletes - Taesuk Choi (Asian Society of Kinesiology, 2018)
OBJECTIVES This study is to compare of CSAI-2 and frontal muscle EMG according to the performance result of university athletes in fencing epee. METHODS This study was carried out on 11 male and 13 female athletes participating in the fencing epee of University A in Seoul. The study subjects were selected based on age and gender. EMG was measured to measure normal frontal EMG, pre-match EMG and post-match EMG. And electromyography(CSAI-2) was measured just before 30 minutes before the match. CSAI-2 mean value, mean and variance of frontal EMG were statistically analyzed by 2-Ways ANOVA. RESULTS First, This study compared with CSAI-2, there was a statistically significant difference confidence among the three factors of competitive state anxiety in the main effect of performance result (p < .01). There were no statistically significant differences in the cognitive state anxiety and physical state anxiety factors between the male and female groups, and the performance group effect. Second, There was a statistically significant difference in normal frontal EMG dispersion in the main effect of gender(p < .05). The main effect of the performance result was statistically significant in frontal EMG average (p < .05). There was a statistically significant difference in the normal average (p < .05) on the interaction between performance and gender. CONCLUSIONS Further research on the application and effect of the training program to improve the performance of the fencing is needed to find out the factors that affect not only the state anxiety, but also physique, physical fitness factor.